Accuracy and Readability in The Translation of Online International Advertisement - Khafidhta Qudsiana Nurul Arifah; Atik Astrini; Winda Sri Handayani; Anam Sutopo; Dwi Haryanti (Samudra Publisher, 2024)
This article explores the intricate process of translating advertisements, emphasizing the importance of linguistic accuracy and cultural relevance in order to effectively convey message between languages. This article highlights the profound influence of advertising language on consumer behavior and the importance of maintaining a balance between precision and coherence. This study uses a literature review methodology to examine various theories and principles related to translation accuracy and readability in advertisements. Key findings reveal that effective advertisement translations must maintain the integrity of the original message while remaining culturally sensitive and engaging. The study highlights five key strategies in translation: transliteration, condensation, addition, recreation, and repetition, as important tools for translators. These strategies ensure that the translation of the advertisement is not only accurate but also resonates well with the target audience, improving its recall and impact. This article concludes that understanding and applying these translation techniques is essential for successful advertising in the global market.